2011
DOI: 10.1021/ic2016484
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Complexes Supported by an [OSSO]-Type Bis(phenolato) Ligand Based on a trans-Cyclooctanediyl Platform: Synthesis, Structures, and 1-Hexene Polymerization

Abstract: trans-Cyclooctanediyl-bridged [OSSO]-type ligand 4 reacts with TiCl(4)(thf)(2) in toluene to produce the corresponding titanium(IV) dichloro complexes as an inseparable mixture of cis-α isomer 6a and cis-β isomer 6b in a ratio of 2:1, whereas treatment of dilithio salt of 4 with TiCl(3)(thf)(3) in Et(2)O afforded chloride-bridged dimeric titanium(III) complex 8, which indicated the antiferromagnetic character in a nonpolar solvent solution. Di(isopropoxy) titanium(IV) complex 10 having a C(2)-symmetric cis-α c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…The Al1–C1 bond length in 4 (1.953(2) Å) is close to those in reported [OSO]- and [OSSO]-type aluminum complexes (1.930–1.948 Å) and noticeably shortened relative to those of the corresponding five-coordinated methyl aluminum complexes incorporating [ONNO]-type ligands within the range 1.963–1.972 Å. , The S–C–C–S dihedral angle (67.81(13)°) deviates somewhat from the ideal 60° of the gauche conformation. Similar deviations, attributed to the conformation of cyclooctane rings, were observed in starting [OSSO]-type ligand 3 (75.3(3)°) and the related [OSSO]-type metal complexes (63.9(2)–76.7(3)°). …”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The Al1–C1 bond length in 4 (1.953(2) Å) is close to those in reported [OSO]- and [OSSO]-type aluminum complexes (1.930–1.948 Å) and noticeably shortened relative to those of the corresponding five-coordinated methyl aluminum complexes incorporating [ONNO]-type ligands within the range 1.963–1.972 Å. , The S–C–C–S dihedral angle (67.81(13)°) deviates somewhat from the ideal 60° of the gauche conformation. Similar deviations, attributed to the conformation of cyclooctane rings, were observed in starting [OSSO]-type ligand 3 (75.3(3)°) and the related [OSSO]-type metal complexes (63.9(2)–76.7(3)°). …”
Section: Resultssupporting
confidence: 70%
“…Beyond the ubiquitous [ONNO]-type ligands, sulfur-linked bis(phenolate) [OSSO]-type ligands have also proven the formation of six-coordinated cationic aluminum species by Okuda . On the other hand, we have recently reported the development of the new [OSSO]-type ligand 1 based on a trans -1,2-cyclooctanediyl platform, along with the synthesis of several group 4 and 5 transition-metal complexes (Scheme ). Upon activation with B(C 6 F 5 ) 3 or (Ph 3 C)[B(C 6 F 5 ) 4 ], dibenzylzirconium complex 2 achieved high activity up to 2500 g mmol –1 h –1 and complete isospecific polymerization of 1-hexene ([ mmmm ] >95%) . Moreover, the dibenzylhafnium complex 3 upon activation with dMAO (dried methylaluminoxane) led to the combination of high activity and controlled isotacticity in the polymerization of 1-hexene, 4-methyl-1-pentene, and propylene .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have succeeded in the development of an [OSSO]-type bis(phenolate) ligand ( 4 ) based on a trans -1,2-cyclooctanediyl platform and the preparation of several early-transition metal and aluminum complexes [43,44,45,46,47,48]. We have also found that zirconium(IV) and hafnium(IV) complexes 5 [49,50] and 6 [51] incorporating ligand 4 with activator could promote precisely isospecific polymerizations of α-olefins such as 1-hexene, 4-methyl-1-pentene, and propylene involving excellent activity (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, dianionic [OSSO]-type tetradentate ligands, based on two phenoxide frameworks with two sulfur donors at the ortho-or benzyl-positions have been of great interest so far . We have reported several Group 4 and 5 metal complexes having an original [OSSO]-type bis(phenolate) ligand possessing a trans-1,2-cyclooctanediyl platform [38][39][40][41][42][43][44][45]. The combination of these complexes and activators could achieve the controlled isotactic polymerization of various α-olefins involving excellent activity.…”
Section: Introductionmentioning
confidence: 99%